2013
DOI: 10.1016/j.neuroimage.2012.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Co-localizing linguistic and musical syntax with intracranial EEG

Abstract: Despite general agreement on shared syntactic resources in music and language, the neuroanatomical underpinnings of this overlap remain largely unexplored. While previous studies mainly considered frontal areas as supramodal grammar processors, the domain-general syntactic role of temporal areas has been so far neglected. Here we capitalized on the excellent spatial and temporal resolution of subdural EEG recordings to co-localize low-level syntactic processes in music and language in the temporal lobe in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 134 publications
2
43
0
1
Order By: Relevance
“…Many previous studies have reported on brain activity elicited by violations of cadences caused by replacing T chords with other irregular chords [1,[10][11][12]16]. The difference in neural responses to less-expected chords compared with expected chords appeared as P3, an early right anterior negativity, or as a late frontal negativity (N5).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many previous studies have reported on brain activity elicited by violations of cadences caused by replacing T chords with other irregular chords [1,[10][11][12]16]. The difference in neural responses to less-expected chords compared with expected chords appeared as P3, an early right anterior negativity, or as a late frontal negativity (N5).…”
Section: Discussionmentioning
confidence: 96%
“…Much neuroscience research on the recognition of musical termination has been concerned with neural activity following the expectancy violation of musical cadences [10][11][12]. These reports show that the chord sequence of the cadence elicits a strong expectation of a T chord at the end of the sequence that induces music termination.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method to examine the contribution of the STGs to the linguistic and musical syntax, Sammler et al [47] compared the early negativities evoked by violations of structure in sentences and chord sequences in five patients. The results showed considerable overlap in the bilateral STG, but also differences in the hemispheric timing and relative involvement of the frontal and temporal brain structures.…”
Section: (C) Intracranial Recordingsmentioning
confidence: 99%
“…Numerous studies in the domains of language, music, and vision have investigated the discrimination of hierarchical structures by asking participants to evaluate whether sequences of items are well‐formed according to a previously learned system of rules (Bahlmann, Schubotz, & Friederici, ; Bahlmann, Schubotz, Mueller, Koester, & Friederici, ; Bianco et al, ; Friederici, Bahlmann, Friedrich, & Makuuchi, ; Maess, Koelsch, Gunter, & Friederici, ; Sammler, Koelsch, & Friederici, ). These studies suggest that lateral prefrontal cortex (PFC, particularly inferior frontal gyrus, IFG) might contribute multi‐domain resources to the processing of hierarchies (Fadiga, Craighero, & D'Ausilio, ; Friederici et al, ; Patel, ), in interaction with areas along ventral visual/auditory streams that may store domain‐specific schematic information (Bianco et al, ; Martins et al, ; Oechslin, Gschwind, & James, ; Pallier, Devauchelle, & Dehaene, ; Sammler et al, ). Recent anatomical research has shown that IFG in humans is expanded (Schenker et al, ) and more strongly connected with the posterior temporal regions in comparison to other primates (Neubert, Mars, Thomas, Sallet, & Rushworth, ; Rilling et al, ).…”
Section: Introductionmentioning
confidence: 99%